The implementation of person-centred plans in the community-care sector: a qualitative study of organizations in Ontario, Canada - Samina Idrees; Gillian Young; Brian Dunne; Donnie Antony; Leslie Meredith; Maria Mathews (BMC, 2024)
Abstract Background Person-centred planning refers to a model of care in which programs and services are developed in collaboration with persons receiving care (i.e., persons-supported) and tailored to their unique needs and goals. In recent decades, governments around the world have enacted policies requiring community-care agencies to adopt an individualized or person-centred approach to service delivery. Although regional mandates provide a framework for directing care, it is unclear how this guidance is implemented in practice given the diversity and range of organizations within the sector. This study aims to address a gap in the literature by describing how person-centred care plans are implemented in community-care organizations. Methods We conducted semi-structured interviews with administrators from community-care organizations in Ontario, Canada. We asked participants about their organization's approach to developing and updating person-centred care plans, including relevant supports and barriers. We analyzed the data thematically using a pragmatic, qualitative, descriptive approach. Results We interviewed administrators from 12 community-care organizations. We identified three overarching categories or processes related to organizational characteristics and person-centred planning: (1) organizational context, (2) organizational culture, and (3) the design and delivery of person-centred care plans. The context of care and the types of services offered by the organization were directly informed by the needs and characteristics of the population served. The culture of the organization (e.g., their values, attitudes and beliefs surrounding persons-supported) was a key influence in the development and implementation of person-centred care plans. Participants described the person-centred planning process as being iterative and collaborative, involving initial and continued consultations with persons-supported and their close family and friends, while also citing implementation challenges in cases where persons had difficulty communicating, and in cases where they preferred not to have a formal plan in place. Conclusions The person-centred planning process is largely informed by organizational context and culture. There are ongoing challenges in the implementation of person-centred care plans, highlighting a gap between policy and practice and suggesting a need for comprehensive guidance and enhanced adaptability in current regulations. Policymakers, administrators, and service providers can leverage these insights to refine policies, advocating for inclusive, flexible approaches that better align with diverse community needs.